Civil society engages African plan - Ernest Harsch (Africa Renewal, 2004)
In the Southern African country of Malawi, most local civil society organizations were initially very critical of the New Partnership for Africa’s Development (NEPAD). Activists objected that the continental development plan was “top-down,” having been drafted by a handful of presidents and then adopted by African leaders, without public consultation, in 2001. They complained that its accent on promoting foreign investment and trade ignored the constraints facing especially poor countries such as Malawi.